Geographical differences in osteoporosis, obesity, and sarcopenia related traits in white American cohorts - Yu Zhou (Nature Portfolio, 2019)
Abstract It has been reported that geographical variation influences bone mineral density (BMD), obesity, and sarcopenia related traits in other countries. However, there is lack of similar studies in the US population. In this study, we compared data from three US study cohorts to evaluate geographical variations of BMD and body composition. BMD, fat mass and lean mass were collected from Dual-energy X-ray absorptiometry machine. ANCOVA and Chi-square tests were used to compare the differences between BMDs, obesity and sarcopenia related traits from different regional sites (Omaha, Kansas City and Baton Rouge/New Orleans). Eta-squared was used to measure the effect sizes of these differences. A total of 11,315 Caucasians from our previous three study cohorts were compared. There was no significant geographical difference in BMD for males or females under the criteria of p-values < 0.05 and effect size η2 > 0.01. There were significant geographical differences with medium effect size (p-value < 0.001, 0.01 < η2 < 0.14) for whole body fat mass percentage and index of low muscle mass. For Caucasians in the United States, there is no significant geographical effect found on BMD. The obesity and sarcopenia related traits are significantly different between the three study cohorts.